2014
DOI: 10.1016/j.virusres.2014.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of viral (zucchini yellow mosaic virus) genetic diversity during systemic movement through a Cucurbita pepo vine

Abstract: Determining the extent and structure of intra-host genetic diversity and the magnitude and impact of population bottlenecks is central to understanding the mechanisms of viral evolution. To determine the nature of viral evolution following systemic movement through a plant, we performed deep sequencing of 23 leaves that grew sequentially along a single Cucurbita pepo vine that was infected with zucchini yellow mosaic virus (ZYMV), and on a leaf that grew in on a side branch. Strikingly, of 112 genetic (i.e. su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 60 publications
1
11
0
2
Order By: Relevance
“…Interestingly, the presence of an additional A residue in this motif was also detected in libraries of PPV-derived small RNAs (not shown). Besides, published data on another potyvirus, Zucchini yellow mosaic virus, showed a minor variant with an extra A in all samples of a Cucurbita pepo vine studied by deep sequencing of long RNAs (13), and our analysis located this modification in the PIPO GA 6 motif as well.…”
supporting
confidence: 65%
“…Interestingly, the presence of an additional A residue in this motif was also detected in libraries of PPV-derived small RNAs (not shown). Besides, published data on another potyvirus, Zucchini yellow mosaic virus, showed a minor variant with an extra A in all samples of a Cucurbita pepo vine studied by deep sequencing of long RNAs (13), and our analysis located this modification in the PIPO GA 6 motif as well.…”
supporting
confidence: 65%
“…The mean frequency of an “A” insertion at the GA 6 site was 0.8%, with frequencies for individual samples ranging from 0.3 to 1.0% ( Appendix Fig S3 ). Similarly, a low level (1–2%) of frameshift mutations at position 2,891 (which corresponds to the GA 6 site) has been reported for Zucchini yellow mosaic virus 20 .…”
Section: Resultsmentioning
confidence: 62%
“…These describe features of gene populations, using mathematical models, and compare observed features with those likely to result from sequential random changes. Popgen analyses have been used to study potyvirus populations within plant populations (e.g., Achon [64]; Li et al [65]; Wang et al [66]; Hajizadeh et al [67]) and, increasingly, virus populations within individual plants (e.g., Cuevas et al [68]; Domingo and Perales [69]; Dunham et al [70]; Kutnjak et al [71]; Rousseau et al [72]; Seo et al [73]). Such studies have shown that the effective populations of potyviruses are all around 10,000 [74], and the "The high potential for genetic variation in plant viruses need not necessarily result in high diversity of virus populations.…”
Section: Population Geneticsmentioning
confidence: 99%